Solar Powered Drying and Hygienic Shoe Rack - Omar, Muhammad Edry; Muhammad Soomro, Dur (Evolution in Electrical and Electronic Engineering, 2023)
This study presents the design and evaluation of a solar-powered closed shoe rack for drying and deodorizing shoes that are wet due to heavy rain or sweating. The shoe rack utilizes airflow to eliminate moisture and odors. The rack is powered by solar panels and is confined in the closed rack to trap heat for more efficient drying. The design includes an automatic fan system that turns on which creates airflow and heating the shoe rack when the shoes are placed inside. The study includes a detailed examination of the design, materials, and functionality of the shoe rack, as well as a comparison of its performance to traditional methods of drying shoes. The study includes an evaluation of the solar-powered closed shoe rack's performance, energy efficiency, and durability. The shoe rack is also able to be controlled via IoT by the application of Blynk Console. It can control the operations of the fans and monitor battery percentage and the duration of the drying process. The results show that the solar-powered closed shoe rack is a convenient and eco-friendly solution for drying and deodorizing shoes, with the added benefit of being energy-efficient and durable. It is also convenient for users as it can be controlled and monitored remotely from their smartphones. Based on this project, the solar-powered closed shoe rack can dry the shoes without the risk of bad smell as well as protect shoes from thieves and avoid being stolen. The study suggests that this technology has the potential to be used in various settings such as homes, gyms, and sports clubs. After several tests, it is found that the shoe rack is effective at drying wet shoes over some time. The drying starts at 10 p.m. with the condition of the shoe being wet at very high humidity (60% g.m-3 or more) and the temperature inside the shoe rack is at 27oC. Considering ideal conditions (normal weather, good indoor air circulation, and optimum shoe rack performance), the shoe will be in a completely dry state at 9 a.m. where the inner shoe rack temperature is 29oC and the estimated humidity of the shoe is below 30% g.m-3 or less. On top of that, the solar charging and battery capabilities are promising as well.